Venture Financier Funding: Study Of Malaysian Technology Based Firms - V., Prathaban (2001)
This study focuses on the small entrepreneurial firms in Malaysia and how the environment makes access to venture capital difficult for them. Despite having sufficient venture funds, there is only a small quantum of investment in these firms.